Plan de negocio para la creación de una microempresa que brinde asesoría comercial y tributaria a los negocios del cantón Playas - Flores Morales, Minely Pamela (2018)
The present project was aimed at the design of a business plan for the creation of a microenterprise that provides business and tax advice to small businesses in the Playas district, its main objective being to determine the approaches for the start-up establishment. The investigation was justified by the commercial potential of the mentioned canton, counting on one of the most important tourist attractions in the entire province of Guayas. However, entrepreneurs have not been able to take advantage of this potential, showing interest in commercial and tax advice, which favors their sales while complying with the laws of the country regarding the registration of their operations………..